Intraoperative neurophysiology multimodality techniques during skull-base surgery. Issue 1 (January 2019) - Tramontano, V.; Masotto, B.; Squintani, G.; Sala, F.
Abstract : Intraoperative Neurophysiological mapping and monitoring techniques, respectively, recognize and preserve both motor and corticobulbar pathway during skull-base surgery. A 25-year old male was admitted to our department for a brainstem cavernoma of the left pons. The patient presented with right hemiparesis and facial nerve palsy. During surgery we applied: (1) upper and lower extremity muscle motor evoked potentials (mMEPs) and last cranial nerves corticobulbar MEPs (CBT-MEPs) by Transcranial Electrical Stimulation (TES) with a short train of stimuli technique (duration 0.5 ms, ISI 2–4 ms, 1 Hz rate and intensity up to 200 mA); (2) direct brainstem mapping technique (hand-held concentric bipolar probe, 1 Hz rate, duration 0.5 ms, stimulation intensity 0.1–5 mA). Although neither mMEPs nor CBT-MEPs were recordable due to the neurological pre-operative deficits, direct brainstem mapping allowed to identify a safe entry zone to the pons. The cavernoma was totally removed and no new or worsen neurological deficits occurred. Vice versa, the pre-existing hemiparesis improved over time. Whenever pre-existing neurological deficits may compromise the success of monitoring techniques, direct mapping could be extremely valuable to avoid injuring the brainstem. To prepare for a multimodality, monitoring and mapping, strategy offers more chances for a valuable neuromonitoring.